Tax Ruling Regulations in Poland – Evolution of the Institution and Evaluation of the Regulations - Ambrożej, Elżbieta Agnieszka (Public Governance, Administration and Finances Law Review, 2018)
This contribution deals with tax ruling in Poland, its evolution, evaluation of legal solutions concerning it, as well as the practice of issuing those rulings by competent tax authorities. The main objective of the contribution is to confirm the hypothesis that legal regulations concerning tax ruling provisions and the practice of issuing them did not sufficiently ensure the main purpose of the ruling, i.e. uniformity of application of tax law by the fiscal apparatus, as well as legal security of taxpayers. The research used a dogmatic and legal research method, which was supplemented by an analysis of the case law of administrative courts and the Constitutional Tribunal, as well as the existing statistical analysis.